A new species of Litarcturus Brandt, 1990 (Crustacea: Isopoda: Valvifera: Antarcturidae) from central Japan - Okumura, Yuzumi; Nakano, Tomoyuki; Shimomura, Michitaka (Zootaxa, 2026)
Litarcturus kumanoensis sp. nov. is described from the Kumano Basin, Japan. Litarcturus kumanoensis sp. nov. is distinguished from other members of the genus by these characters: head with 2 supraocular and 2 blunt posterior supraocular spines; pereonite 1 with 2 submedial and sublateral spines; pereonites 2 to 7 each with 2 short submedial spines; pleonites 1 and 2 each with 2 submedial spines; pleonite 3 with 2 submedial and lateral spines; pleotelson pentagonal, with 4 submedial, 1 sublateral spines and 2 caudolateral spines. This is the second species of the genus to be described and found in Japan. An amended generic diagnosis is provided.